Chinese Physicians’ Preference for Prescribing Brand-Name vs. Generic: A Discrete Choice Experiment - Wang, Ruilin; Wang, Zhiyuan; Li, Xiaoyu; Bai, Lin; Fan, Pingan; Li, Huangqianyu; Tang, Yuanyuan; Li, Xin; Huang, Yangmu; Nie, Xiaoyan; Shi, Luwen; Chen, Jing (International journal of health policy and management, 2024)
Background: Promoting the use of generic drugs is a viable strategy to control drug costs. As physicians have a critical role in deciding on what drugs to prescribe and thus whether certified generic drugs were actually used, this study aimed to analyze factors influencing whether physicians were willing to prescribe generic drugs versus brand-name drugs after the implementation of Consistency Evaluation Policy (CEP). Methods: A discrete choice experiment (DCE) was developed to explore factors influencing physicians’ preferences toward prescribing brand-name drugs versus its certified generic. There were four attributes in the model, namely prices, hospital-level cost control measures, information about clinical safety and efficacy of generic drugs, and reimbursement rate. In total, 1297 physicians from 101 hospitals participated in the study and 1047 questionnaires were retained. Results: We found that substantial disclosed information about the generic’s clinical safety and efficacy (Sufficient information, odds ratio [OR]=3.251, 95% CI=3.098-3.412), lower price of the certified generic (price ratio of generic drugs versus brand-name drugs=1: 10, OR=1.130, 95% CI=1.078-1.185), stringent hospital cost control measures (the brand-name drugs were affected by the national centralized drug procurement (NCDP) policy or a tight cost-control measure, OR=1.247, 95% CI=1.190-1.307), and lower reimbursement rates for brand-name drugs (reimbursement rate=20%, OR=1.283, 95% CI=1.224-1.346) all increased physicians’ propensity to prescribe certified generic drugs. Conclusion: When certified generic drugs were lower priced or disclosed more information about their clinical safety and efficacy or when brand-name drugs were subject to tighter hospital cost control measures, physicians were more inclined to prescribe certified generic drugs. The findings suggest that CEP, together with the NCDP to promote market competition and hospital cost control measures targeting brand-name drugs, promoted the use of generic drugs through influencing physician prescribing behavior. The widely use of generic drugs may further benefit from increased disclosure of the clinical safety and efficacy of generic drugs by their manufacturers.